Increasing the public health voice in global decision-making on nutrition labelling - Thow, Anne M; Jones, Alexandra; Huckel Schneider, Carmen; Labonté, Ronald (Université d'Ottawa | University of Ottawa, 2020)
Abstract To respond to the global noncommunicable disease (NCD) crisis, the Codex Alimentarius Commission (Codex), a multilateral United Nations body responsible for work on food standards, is developing global guidance for front of pack (FoP) nutrition labelling. Guidance from Codex regarding FoP nutrition labelling at the global level will almost certainly influence national policy making. This shift in Codex’s activities towards standards to address NCDs presents new risks for achievement of public health goals, as a result of the high level of industry involvement in this forum; there is a potential commercial conflict of interest held by manufacturers of products whose consumption could be discouraged by such guidance. In this Commentary, we examine the implications of Codex processes for developing robust global guidance on FoP nutrition labelling and identify opportunities to increase consideration of public health objectives. To date, there has been significantly higher representation of food industry compared to public health actors in Codex discussions on FoP nutrition labelling. Without a strong public health voice in Codex, the industry voice could dominate discussions on FoP nutrition labelling, such that subsequent global guidance prioritises future trade and profits over potential risks to public health. There is currently a critical window of opportunity for public health interests to be prioritised in this multisectoral international forum. The key public health priority for global guidance on FoP nutrition labelling is to ensure protection of policy space for national governments to implement strong and effective regulation, and allow scope for innovation. Public health actors can engage directly with Codex processes, at both the national and global level, and also need to raise awareness among domestic policy makers – including with Ministries of Agriculture and Industry, which often represent countries at Codex – regarding the importance and effectiveness of FoP labelling in NCD prevention. Increased engagement with Codex processes represents a tangible new opportunity to strengthen global governance for public health, and move towards improved coherence between trade policy and health protection goals.